Value of Hematological and Coagulation Parameters as Prognostic Factors in Acute Coronary Syndromes - Elena Emilia Babes; Dana Carmen Zaha; Delia Mirela Tit; Aurelia Cristina Nechifor; Simona Bungau; Felicia Liana Andronie-Cioara; Tapan Behl; Manuela Stoicescu; Mihai Alexandru Munteanu; Marius Rus; Mirela Marioara Toma; Ciprian Brisc (Diagnostics, 2021)
The values of hematological and coagulation biomarkers were evaluated as predictors of in hospital mortality and complications, in patients with acute coronary syndromes (ACS). This retrospective observational study enrolled 936 ACS subjects admitted to the Clinical Emergency Hospital of Oradea, Romania, between January–December 2019. Hematological and coagulation parameters were obtained at admission. During hospitalization, the following adverse events were recorded: death, ventricular rhythm disturbances, atrial fibrillation, heart failure, re-infarction, and stroke. Accuracy of hematological and coagulation parameters as predictors of adverse outcome were also evaluated. The diagnosis was unstable angina in 442 patients (47.22%), non-ST-elevation myocardial infarction (NSTEMI) in 113 patients (12.1%) and ST-elevation myocardial infarction (STEMI) in 381 patients (40.70%); 87 patients (9.29%) died during hospitalization and 193 (20.7%) developed complications. Predictors for in hospital mortality were as follows: red cell distribution width (RDW) (AUC 0.691, p < 0.0001), white blood cells (WBC) (AUC 0.684, p < 0.0001), neutrophils (NEU) (AUC 0.684, p < 0.0001), and prothrombin time (PT) (AUC 0.765, p < 0.0001). WBC (AUC 0.659, p < 0.0001), NEU (AUC 0.664, p < 0.0001), RDW (AUC 0.669, p < 0.0001), and PT (AUC 0.669, 95% CI 0.622–0.714, p < 0.0001) also had accuracy for complications prediction. RDW had a good ability to predict heart failure in NSTEMI patients (AUC 0.832, p < 0.0001). An acceptable ability to predict ventricular rhythm disturbances occurrence had WBC (AUC 0.758, p < 0.0001) and NEU (AUC 0.772, p < 0.0001). Hematological and coagulation parameters can help in risk stratification of ACS patients. RDW, WBC, NEU, and PT were able to predict mortality and in-hospital complications in ACS patients. RDW has a good accuracy in predicting complications and heart failure in NSTEMI patients. WBC and NEU are good predictors for ventricular rhythm disturbances.